Ecological niche modeling approach for assessing potential for expansion of irrigated rice under alternate wetting and drying method - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The approach was developed and validated for irrigated schemes of Burkina Faso. The evaluation metrics of the machine learning approach showed values higher than 80%. The schemes and seasons suitable for AWD were validated against ground truth data. The validated approach can be applied to the whole West African region.